(untitled) (Devenires, 2011)
In the article that opens this issue of becomings, master Luis Villoro addresses an important aspect of the novel by Miguel de Cervantes: the relationship between reality and poetic creation. I hope not to distort its central idea if I condenso thus: the reality imagined by the novel —or poetry— is a transfigured reality manifests itself by the excitement and enthusiasm that pointing out what it is called reality is a delusion, beat beating this and creating a higher reality imagined. I suggest that some of the reasons why don Quixote in a maker of new realities from the reality that manages transfigurar, based on book, Reading and the new literary genre Announces. Don Quixote is a multitude of books and a book in which the reference to the books is constant. And there are no books without readers, is worth mentioning the fact that social differences no implied a different culture; cultural elites paid attention to the rich oral literature and illiterates were not excluded know most popular literary works of the time by reading out loud made of them.